Analisis Ketepatan Waktu Penyampaian Laporan Keuangan Kepada Publik: Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2017-2020 - Alvia Fauzani; Rida Rahim (Fakultas Ekonomi Universitas Andalas, 2022)
This study aims to determine the factors that affect the timeliness of submitting financial reports to companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2017-2020 period. The population in this study were all consumer goods industrial companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used in this research is non-probability sampling by using purposive sampling method with certain criteria. The research sample is 46 companies with a total of 184 observations. This study was tested using logistic regression analysis. Timelines (measured by a dummy variable, 1 if the company fulfills the submission of financial statements) is before and on March 31, while 0 for delayed submission). The results of hypothesis testing from this study indicate that profitability, institutional ownership, age have a significant effect on the timeliness of submitting financial statements. While leverage has a significant negative effect on timeliness, and company size, KAP size, education have no significant effect on the timeliness of submitting financial statements.